What do European employers' organisations do? - Mona Aranea; Leon Gooberman; Marco Hauptmeier (Hans-Böckler-Stiftung, 2021)
This paper identifies four roles of contemporary European Employers' Organisations. European Employers' Organisations are lobbyists in Brussels that represent the interests of their members, seeking to influence institutions. European Employers' Organisations are reluctant social partners that engage with labour unions, though mostly with the aim to avoid binding regulation. European Employers' Organisations are service providers, amongst others informing members about EU legislative and programmatic developments. Finally, European Employers' Organisations are standard setters in Europe, focussing on voluntary, flexible norms and codes of conduct.
Keywords: 330; Employer's Organisations; EEO; Lobbying; Employer representatives; Employment relations